Competitiveness in the classroom: a case study with the seventh grade - Venga Pereira, Sthefano (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Since 1980, with the phenomenon of globalization and the strengthening of neoliberal ideals, education began to be influenced by a process of commercialization of its actions, methods and functions. Its main objective was no longer the transformation of society and the fair and integral formation of individuals, but to meet the economic and competitive demands of the market. This case study used different data collection instruments, such as surveys and semi-structured interviews. The research is of a mixed nature and investigates the competitiveness of seventh grade students of an educational institution in Zipaquirá, Colombia. The results obtained showed a strong presence of competitive behaviors among students. In addition, the results explain that competitiveness in the group is due to factors such as individualism, encouraged by neoliberalism, parental pressure for high academic results, work aspirations and bullying.